INCREASING THE COMPANY'S PROFITABILITY AND COST EFFICIENCY THROUGH THE IMPLEMENTATION OF ACTIVITY-BASED MANAGEMENT, VALUE CHAIN, AND PESTEL - Demsina Sinaga, Yanti; A. Hermawan, Ancella (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
The purpose of this research is to analyze and evaluate whether the costs incurred by the company can meet the established cost standards and how its implementation can reduce and eliminate all activities that are not value-added to all costs, especially import and distribution activities to customers, resulting in cost reductions that increase competitive advantage and maximize profitability. The analysis of this research is descriptive qualitative in the form of a case study through obtaining data from observation, interviews, and documentation. The findings show a cost difference between the traditional methods implemented by the company and the cost of reaching the standards set with Activity Based Management. Furthermore, the company reduces non-value-added activities in importing and shipping goods to customers to win the competition. It establishes a PESTEL strategy for analyzing the inhibiting factors of market competition.